Activation of Macrophages by Oligomeric Proteins of Different Size and Origin - Dalgėdienė, Indrė; Lučiūnaitė, Asta; Žvirblienė, Aurelija (Mediators of Inflammation, 2018)
Activation of macrophages is one of the key processes in generating the immune response against pathogens or misfolded/aggregated otherwise unharmful host’s proteins. Antigens and their immune complexes (IC) may shape macrophage phenotype in various directions. Data on the impact of protein structure during inflammation are evident; however, some separate steps of this process involving changes in macrophage phenotype are not fully understood. Our aim was to investigate the phenotype of macrophages after activation with different oligomeric proteins and their IC. We have used amyloid beta (Aβ1–42) that plays a role in neurodegenerative inflammation as a model of host-associated protein and three oligomeric viral antigens as pathogen-associated proteins. Murine cell lines J774, BV-2, and macrophage primary cell culture were treated with oligomeric proteins and their IC. After 48 h, expression of surface markers F4/80, CD68, CD86, and CD206 and secreted cytokines IL-10, IL-12, IL-23, and TNF-α was analysed. Aβ1–42 oligomers stimulated expression of both inflammatory and anti-inflammatory molecules; however, fibrils induced less intense expression of markers investigated as compared to small and large oligomers. Two out of three viral oligomeric proteins induced the inflammatory response of macrophages. Data suggest that macrophage activation pattern depends on the origin, size, and structure of oligomeric proteins.